Analysis and Mapping of Changes in Salinity Concentration Influence by Acidity Value in Kwanyar Coastal, Bangkalan Madura District - Siti Zainab; Novie Handajani; Hendrata Wibisana (Nusantara Science and Technology Proceedings)
Kwanyar in Bangkalan Madura district is an area that is not very fertile, the soil contains limestone and the coastal areas of the coast are the result of reclamation for several years. Thus, what used to be water areas turn into land. The purpose of this research is to map and analyze the effect of changes in acidity values on the coast with changes in salinity values that accompany them so that the most suitable mathematical model can be found to describe the coastal conditions of the Kwanyar area. The method developed to map and analyze is the use of remote sensing technology using Terra MODIS satellite imagery with a pixel resolution of 1 kilometer. The results obtained from a series of measurements carried out are that the most suitable wavelength for salinity mapping is 667 nanometers with an exponential mathematical model. This study concludes that the value of acidity in the aquatic environment is statistically sufficient to influence changes in the concentration of salinity in the Kwanyar area, Bangkalan Madura district